Enhancing Theory of Mind Skills: Intervention Strategies for Individuals with Autism - Payel Dey Ghosh; Mallika Banerjee (Current Progress in Arts and Social Studies Research Vol. 4, 2024)
Theory of Mind (ToM) is the ability to understand another’s perspective. It has two components- cognitive and affective. The cognitive component means understanding others’ beliefs, intentions, perspectives, etc. and the affective component indicates knowledge regarding emotions. Impairment in ToM is one of the major features of Autism. Autism is a neurodevelopmental disorder characterized by impaired communication and Socialization. Individuals with Autism experience difficulties in understanding the intentions, beliefs, and perspectives of other individuals because of their limited ToM skills, and they also find it difficult to predict the emotions of another individual. Therefore, structured interventions are required to improve ToM skills in individuals with Autism. The present study focuses on different ToM intervention methods and the effectiveness of those methods. However, the present review observes that most of the interventions are suitable for individuals with high-functioning Autism. Besides these interventions are heavily loaded with language and therefore these interventions are not suitable for the nonverbal group. Thus, most of the individuals with Autism are out of the scope of these interventions. Therefore, ToM interventions suitable for nonverbal and low-functioning groups of Autism are required.